2016
DOI: 10.1016/j.cllc.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preradiotherapy 18F-FDG PET/CT Volumetrics in Limited-Stage Small-Cell Lung Cancer

Abstract: Background Whether FDG PET/CT metrics predict outcome in limited-stage small cell lung cancer (LS-SCLC) has not been well established; most previous reports have only analyzed SUVmax. We investigated multiple pre-treatment PET metrics, including SUVmax, SUV mean, total lesion glycolysis (TLG), and metabolic tumor volume (MTV) in LS-SCLC patients undergoing chemoradiotherapy (CRT) and correlated them with survival and disease control outcomes. Methods All patients received platinum-based chemotherapy and a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…), and that from the fixed effects model was 2.10 (95% CI 1.77–2.50). There was a high level of heterogeneity among the six studies ( I 2 = 87%) . The combined HR of TLG for OS from the random effects model was 1.61 (95% CI: 1.24–2.07; Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…), and that from the fixed effects model was 2.10 (95% CI 1.77–2.50). There was a high level of heterogeneity among the six studies ( I 2 = 87%) . The combined HR of TLG for OS from the random effects model was 1.61 (95% CI: 1.24–2.07; Fig.…”
Section: Resultsmentioning
confidence: 95%
“…We reviewed the remaining full text for nine articles; one study that calculated the HRs by a 10‐cm 3 increase in MTV and TLG was excluded, while one study was excluded because it did not provide data for HRs and lacked sufficient information to enable a calculation of the HR with corresponding 95% CI . The remaining seven articles all conformed to the inclusion criteria and had sufficient information to allow calculation of HRs . Both MTV and TLG were measured in three studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analysis of small retrospective and nonrandomized prospective studies demonstrated the prognostic significance of pretreatment 18 F-FDG PET volumetric and metabolic parameters in SCLC, 35 but these results are inconsistent. 36 Complete data on pretreatment 18 F-FDG PET parameters in our study were unavailable. A separate exploratory analysis on the prognostic significance of 18 F-FDG PET volumetric and metabolic parameters in patients recruited to CONVERT from UK centers is ongoing.…”
Section: F-fdg Pet/ct Is Not As Well Established In Sclcmentioning
confidence: 98%